2011
DOI: 10.1177/1460458211405809
|View full text |Cite
|
Sign up to set email alerts
|

Why patient summaries in electronic health records do not provide the cognitive support necessary for nurses’ handoffs on medical and surgical units: Insights from interviews and observations

Abstract: Patient care handoffs are cognitively intense activities, especially on medical and surgical units where nurses synthesize information across an average of four to five patients every shift. The objective of this study was to examine handoffs and nurses' use of computerized patient summary reports in an electronic health record after computerized provider order entry (CPOE) was installed. We observed and audio taped 93 patient handoffs on 25 occasions on 5 acute care units in 2 different facilities sharing a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 51 publications
0
86
0
2
Order By: Relevance
“…Strople and Ottani [11] made a good case for the desirability of using computers to at least partially automate the shift handover process, but did not describe or evaluate an actual system. However, Staggers et al [12] found that the computerised patient summary report and the electronic health record were minimally used during the handover and that the existing patient summary reports did not provide adequate cognitive support for nurses. They found that patient summary reports were incomplete, rigid and did not offer "at a glance" information, or help nurses encode information.…”
Section: Computerised Shift Handovermentioning
confidence: 99%
“…Strople and Ottani [11] made a good case for the desirability of using computers to at least partially automate the shift handover process, but did not describe or evaluate an actual system. However, Staggers et al [12] found that the computerised patient summary report and the electronic health record were minimally used during the handover and that the existing patient summary reports did not provide adequate cognitive support for nurses. They found that patient summary reports were incomplete, rigid and did not offer "at a glance" information, or help nurses encode information.…”
Section: Computerised Shift Handovermentioning
confidence: 99%
“…In another case users refrained from using the system because it yielded incomplete, limited personalized information that was not portable, not consistent with human information processing and memorizing and not presented in a way to grasp the main issues at a glance [75]. Documentation systems used for handovers, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the electronic environment supporting the handover process the electronic tool was used to replicate conventional procedures in the majority of the studies, i.e. users still printed out the electronic handover report or wished to do so to allow the use of information in places without computer access or to make personal notes [36,59,62,65,[68][69][70]73,75,77]. Only two studies described a totally different approach to handing over patients.…”
Section: Information Content and Usementioning
confidence: 99%
See 2 more Smart Citations